Who cares: Deciphering China's female employment paradox - Haiyue Yu; Jin Cao; Shulong Kang (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2021)
Female post-childbirth labor market participation and labor intensity are extraordinarily high in China, given that public childcare subsidies are limited and supportive policies for childbearing female employees are largely absent. Establishing a panel dataset that tracks female employment and childbirth, we find that such a paradox is well-explained by the intra-family childcare support provided by grandparents. Correcting the selection bias that stems from women's fertility choices using the propensity score matching difference-in-difference model, we find that women without grandparental support suffer a substantial drop in post-childbirth employment, while women with grandparental support even experience a rise in employment after childbirth. It takes women without grandparental support twice as long to recover their employment after childbirth. Finally, we find that childbirth does not decrease women's labor intensity due to a lack of labor market flexibility, and that women face a stay-or-quit dilemma when grandparental childcare support is absent.
URN:NBN:fi:bof-202105191241
Keywords: C24; J13; J22; 330; Financial frictions; management practices; CO2 emissions; energy efficiencygrandparental childcare; PSM-DID; fertility choice; female employment; labor intensity